EXPLORING THE RISK FACTORS ASSOCIATED WITH EMPOROMANDIBULAR DISORDERS: A CROSS-SECTIONAL STUDY AMONG A SAMPLE OF YEMENI PATIENTS - Hajeb, Raji Mansoor; Abdulghani, Mahfoudh A. M; Al-wesabi, Mohammed Ali; Al-Maweri, Sadeq Ali (Malaysian Journal of Public Health Medicine, 2025)
Temporomandibular disorders (TMD) are prevalent orofacial pain conditions, affecting 5% to 70% in the general population. Despite their high prevalence, research on TMD in Yemen is scarce. Qat-chewing, a culturally ingrained habit in Yemen, has been suggested as a potential risk factor for TMD. This study aimed to assess the association of qat-chewing and other risk factors with TMD among patients visiting the Oral Medicine clinic of Sana'a University and Al Kuwait Teaching Hospital, Sana'a, Yemen. A cross-sectional study was conducted involving 148 TMD patients, diagnosed using the Research Diagnostic Criteria for TMD (RDC/TMD). The mean age of participants was 23.9 ± 10.6 years with predominance of females 69.6%. Pain in jaw joints and masticatory muscles was the most frequently reported symptoms (82.4%). Identified risk factors included emotional stress (87.2%), external head trauma (12.8%), parafunctional habits like teeth grinding (21.4%), and qat-chewing (36.5%). The study concludes that emotional stress and qat-chewing are the most significant risk factors for TMD among Yemeni population.